2018
DOI: 10.1002/ece3.4632
|View full text |Cite
|
Sign up to set email alerts
|

Urban forest fragmentation impoverishes native mammalian biodiversity in the tropics

Abstract: Urban expansion has caused major deforestation and forest fragmentation in the tropics. The impacts of habitat fragmentation on biodiversity are understudied in urban forest patches, especially in the tropics and little is known on the conservation value of the patches for maintaining mammalian biodiversity. In this study, camera trapping was used to determine the species composition and species richness of medium‐ and large‐sized mammals in three urban forest patches and a contiguous forest in Peninsular Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Ecological effects originated from edges between forest and non-forest areas create edge effects and alter biophysical features for species, such as radiation, wind and water fluxes and therefore, lead to microclimate change (Estreguil & Mouton, 2009;Sauders et al, 1991). Previous studies on mammal species richness in Selangor state also recorded the absence of large carnivore or top predator (e.g., Malayan Tiger and Melanistic Leopard) both in the contagious forest and fragmented urban forest reserves (Adila et al, 2017;Tee et al, 2018). Because most of the large mammals in the tropics such as rhinoceroses, tigers and elephants, are unlikely to persist in the multiple-use matrix that are subjected to anthropogenic disturbance (Lynam, 2010;Pattanavibool & Dearden, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological effects originated from edges between forest and non-forest areas create edge effects and alter biophysical features for species, such as radiation, wind and water fluxes and therefore, lead to microclimate change (Estreguil & Mouton, 2009;Sauders et al, 1991). Previous studies on mammal species richness in Selangor state also recorded the absence of large carnivore or top predator (e.g., Malayan Tiger and Melanistic Leopard) both in the contagious forest and fragmented urban forest reserves (Adila et al, 2017;Tee et al, 2018). Because most of the large mammals in the tropics such as rhinoceroses, tigers and elephants, are unlikely to persist in the multiple-use matrix that are subjected to anthropogenic disturbance (Lynam, 2010;Pattanavibool & Dearden, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To (Table 2; Table S1-S3). The selection of variables was based on previous studies (Jamhuri et al, 2018;Sasidhran et al, 2016;Tee et al, 2018) that were conducted to assess the mammal species present in a different type of tropical forest. We also used existing ecological information to guide us in selecting several site-level and landscape variables (e.g., elevation, habitat type, type of forest).…”
Section: Assessment Of Site-level and Landscapelevel Variablesmentioning
confidence: 99%
“…Across its range, wild populations of chevrotain or mouse‐deer are declining because of habitat fragmentation, habitat destruction for timber extraction, and poaching (Adila et al, 2017; Heydon & Bulloh, 1997; Jamhuri et al, 2018; Nguyen et al, 2019; Tee et al, 2018). Chevrotain species inhabit primary and secondary lowland rainforests and, in all parts of their range, are hunted for food (Azhar et al, 2014; Luskin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both vertebrate and invertebrate species occurring in forests are under increasing pressure from habitat loss, habitat fragmentation and hunting and/or illegal hunting, that is, poaching (Alroy, 2017;Jamhuri et al, 2018;Newbold et al, 2014;Samantha et al, 2020;Tee et al, 2018). Using satellite imagery, Curtis et al (2018) reported that 27% of global forest loss (~5 million hectares of forest a year), over a fifteen year period (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), can be attributed to deforestation through permanent land use change for commodity production, such as palm oil, mining, oil and gas production extractive industries, and urban expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Both vertebrate and invertebrate species occurring in forests are under increasing pressure from habitat loss, habitat fragmentation and hunting and/or illegal hunting, that is, poaching (Alroy, 2017; Jamhuri et al., 2018; Newbold et al., 2014; Samantha et al., 2020; Tee et al., 2018). Using satellite imagery, Curtis et al.…”
Section: Introductionmentioning
confidence: 99%